Consent and community engagement in diverse research contexts. - Participants in the Community Engagement and Consent Workshop , Kilifi, Kenya , March 2011 (2013)
Consent and community engagement (CE) in health research are two aspects of a single concern-that research is carried out in a respectful manner where social value is maximized. There are important overlaps and interdependencies between consent and CE; for example, CE can provide insights into how best to tailor consent to context and can be an important component of consent processes. Engaging communities can also have intrinsic and instrumental value beyond consent; for example, as a means of showing respect and identifying appropriate ways of working respectfully. In this paper we critically examine how CE and consent processes are characterized, conducted, and evaluated in diverse health research contexts, and propose a preliminary research agenda to support future learning in these critical areas.